Creation of 2-5 keV and 5-10 keV sky maps using XMM-Newton data - Savchenko, D.O.; Iakubovskyi, D.A. (Advances in Astronomy and Space Physics, 2014)
Sky maps are powerful visualisation tools for quicklook analysis of extended sources. The latest sky map in soft X-rays (0.1-2.4 keV) has been created in the 1990's using ROSAT data. By analysing publically available data from XMM-Newton X-ray mission we constructed new sky maps in two energy bands - 2-5 keV and 5-10 keV,complementary to ROSAT data, covering approximately 1% of the sky, and included them in our web-based tool http://skyview.virgoua.org.